The Mediating Effect of the Big Data Analytics on the Relationship between Strategic Service Logistics Management and Operational Performance (Gestão & Regionalidade, 2021)
This paper, of exploratory nature of quantitative type, analyzed customer satisfaction in e-commerce, in particular attention on the mediating effect of the use of the Big Data Analytics in the relationship between strategic management of service logistics and operational performance. Ninety-eight questionnaires were obtained from logistics managers of e-commerce companies. The data treated by structural equation modeling, Partial Least Square, Path Modeling (PLS-PM) technique, at statistical significance level (Î± â‰¤ 0.05), revealed that the Big Data Analytics partially mediated the relationship between strategic service logistics management and logistics operational performance, in turn, positively influenced customer satisfaction. This result presented implications for the theory and management practices.Keywords: big data analytics; strategic logistics management; logistic operational performance.
Keywords: big data analytics; strategic logistics management; logistic operational performance